Analisis Location Quotient (LQ) Komoditas Cabai di Kabupaten Kediri - Cynthia Paramita Astasari; Jabal Tarik Ibrahim; Harpowo Harpowo (Universitas Muhammadiyah Malang, 2018)
Chili is vegetables that have an important role in agriculture in Indonesia. Generally, the amount of chili production is determined by the harvested area and productivity of the land. Chili is one of the main horticulture products in Indonesia. Kediri District is potential as a center of chili’s production. According to Ibrahim, 2012 there are four major sub-district in the production of chili commodities, such as Kepung District, Puncu District, Papar District, and Pagu District. The determination of a commodity to be a superior commodity in Kediri District based on the consideration that not all vegetable commodities are suitable to be developed in all places. The purpose of this research is 1) Knowing the growth of chili’s production, 2) Analyze the Location Quotient of chili in Kediri District, 3) Analyze the Location Quotient of cayenne in Kediri District. This research is using secondary data. This research data was analyzed by Location Quotient (LQ). This research shows that the growth of harvested area has fluctuated every year. Chili’s production has fluctuated during 2014-2016. Cayenne’s production has fluctuated during 2014-2016. Mojo sub-district is basis area of harvested area and chili’s production for last three years. Pagu District sub-district is basis area of harvested area and cayenne’s production for last three years.